ANALISIS PENGARUH POTONGAN HARGA DAN KEMASAN TERHADAP KEPUTUSAN PEMBELIAN KONSUMEN PADA INDOMARET LAHAT - Hasanah, Titi (MOTIVASI, 2021)
Purpose – This study aims to determine: (1) the effect of price discounts on purchasing decisions for Indomaret Lahat consumers (2) the effect of packaging on purchasing decisions for Indomaret Lahat customers. (3) the effect of Price Discounts and Packaging on Purchase Decisions for Indomaret Lahat customers. Design/methodology – This research includes associative or relationship research using a quantitative approach. The population in this study were all consumers who made purchases at Indomaret Lahat. The sampling technique used purposive sampling method with a total sample of 80 people. The data collection technique uses a questionnaire that has been tested for validity and reliability, and the data analysis technique used is multiple regression.  Findings – The results showed that (1) there was a positive effect of price discounts on packaging for Indomaret Lahat consumers, (2) there was a positive influence on packaging on purchasing decisions for Indomaret Lahat consumers.